2011
DOI: 10.1007/s00595-010-4413-y
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyoma of the small intestine in an adult: Report of a case

Abstract: We report a case of adenomyoma in the small intestine, which is an extremely rare entity. An 81-year-old woman presented to our hospital with a history of three episodes of vomiting accompanied by abdominal pain. Upper gastrointestinal examination via a long tube found intestinal obstruction caused by a tumor of the small intestine. Laparotomy revealed a hard mass, 160 cm distal to the Treitz ligament. Pathological examinations of the resected tumor confirmed a diagnosis of adenomyoma originating in the small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Moreover, abdominal bloating symptom coincides with an accumulation of gas produced by a tumor intestinal obstruction, among other causes, as previously found in human [23-25]. In other words, a relationship between those symptoms and bowel tumor can be established.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, abdominal bloating symptom coincides with an accumulation of gas produced by a tumor intestinal obstruction, among other causes, as previously found in human [23-25]. In other words, a relationship between those symptoms and bowel tumor can be established.…”
Section: Discussionsupporting
confidence: 68%
“…Clinically, our case presented with intussusceptions caused by adenomyomas of the ileum. To our knowledge, our case is the first report of two synchronous adenomyomas of small intestine, and the third report of adenomyomas causing intestinal intussusceptions in an adult .…”
Section: Discussionmentioning
confidence: 62%
“…Table 1. Review of the literature: Clinicopathological findings of adenomyoma of the small intestine [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…5 While the incidence of small intestine adenomyoma is relatively rare, the actual incidence is unclear because very few cases have been reported. Review of the literature reveals 34 reported cases in the small intestine, 3,[5][6][7][8][9][10][11][12][13][15][16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34] including the duodenum, ampulla of Vater, and ileum, with 11 well-documented cases reported in the jejunum (Table 1). 3,5,9-10,16-17, 20-21,29,31,34 Of these cases, the patients were between the ages of three to eighty one years old, with six women and five men.…”
Section: Discussionmentioning
confidence: 99%
“…In the periampullary region, adenomyoma typically presents with biliary obstruction or abdominal pain, with reported cases of acute pancreatitis. 14,22 Lesions in the ileum and jejunum have presented with intussusception and intestinal obstruction, 29 but many reported cases have been incidentally detected. In the small intestine, intussusception is its most common complication, reported in 19 cases.…”
Section: Discussionmentioning
confidence: 99%